If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5y + -18 + -4y = -36 Reorder the terms: -18 + 5y + -4y = -36 Combine like terms: 5y + -4y = 1y -18 + 1y = -36 Solving -18 + 1y = -36 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '18' to each side of the equation. -18 + 18 + 1y = -36 + 18 Combine like terms: -18 + 18 = 0 0 + 1y = -36 + 18 1y = -36 + 18 Combine like terms: -36 + 18 = -18 1y = -18 Divide each side by '1'. y = -18 Simplifying y = -18
| 33d=12 | | 16/1-4=x | | 3x-9=-48 | | 14=-7(n+3)-7(n+5) | | 20c=297.20 | | -5=.50x | | 36=5t-14t | | 5-2x=9-4x | | x(2x-5)(3x+1)=0 | | 8x-14=34 | | 16x+4=18x | | 2.2x-8.6=-8.6 | | 90/12=22.50/x | | -8(3n+7)=-40-8n | | -5(-4v-7)=-105 | | 3x^4-2x-1=0 | | 6k+(22)=(6)k+22 | | 21.6y+3+7(0.2y+1.1)+36y-2.5=96,7 | | 19-17=x/-7 | | 7x=9-(-19) | | 5x+7a+4a+2a= | | -4/5+8 | | 2+3=4+7xm | | 7y-5y+4=20 | | p/6=-3 | | (m+6)(m-6)/(m+6)^2 | | 5*18-4j=-36 | | 6w-12w=-54 | | 11-5(10q-12)= | | -50/7+8 | | 5(-2x-2)=-(x-8) | | 2x+13=124 |